Al Qaeda Osama bin Laden's army of terrorists - Margulies, Phillip (New York : Rosen Pub. Group, 2003)
Discusses the Islamic organization known as Al-Qaeda, focusing on its presumed role in the September 11 terrorist attacks in the United States.
Mujahedeen -- Inside al-Qaeda -- September 11 -- The investigation -- Conclusion.
10 - 13 years
Keywords: Qaida (Organization); Terrorism; Jihad; September 11 Terrorist Attacks, 2001.; War on Terrorism, 2001-